Managing Innovation and Marketing in a Globally Dynamic Firm: Best Practices in Management at Diageo - Khan, Idrees Matthew (Advances in Social Sciences Research Journal, 2015)
Organizing and coordinating the activities of a business organization for the purpose of achieving its objectives is the goal of management. As such, management as a whole is extremely important in smoothly running a corporation and maintaining a profitable business. All the day-to-day activities can only be accomplished properly if there is good management in place. It covers all aspects of a business including marketing, daily operations, and innovation. This paper elaborates on the innovation and marketing strategies of Diageo, while using the company as a comparison for highlighting the positives and negatives of using certain management philosophies, practices and concepts that have made them successful in the alcoholic “drinking” industry.